2011
DOI: 10.1088/0004-637x/740/2/81
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological Magnetohydrodynamic Simulations of Cluster Formation With Anisotropic Thermal Conduction

Abstract: The intracluster medium (ICM) has been suggested to be buoyantly unstable in the presence of magnetic field and anisotropic thermal conduction. We perform first cosmological simulations of galaxy cluster formation that simultaneously include magnetic fields, radiative cooling, and anisotropic thermal conduction. In isolated and idealized cluster models, the magnetothermal instability (MTI) tends to reorient the magnetic fields radially whenever the temperature gradient points in the direction opposite to gravi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 80 publications
4
50
0
Order By: Relevance
“…The initial conditions for this cluster were generated from the Millennium XXL simulation (Angulo et al 2012) and then rescaled to the latest Wilkinson Microwave Anisotropy Probe-9 (WMAP-9) measurements (Hinshaw et al 2013 , respectively, with a softening length of 1.4 kpc for both particle types. Our mass resolution is ∼1000 times and our spatial resolution is ∼30 times better than those of previous simulations attempting to model anisotropic thermal conduction in a cosmological context (Ruszkowski et al 2011). We also achieve better resolution than idealized non-cosmological simulations with thermal conduction (Ruszkowski & Oh 2010;Parrish et al 2012;Yang & Reynolds 2016) and recent cosmological pure hydrodynamic simulations of clusters (Hahn et al 2017;Rasia et al 2015).…”
Section: Simulationsmentioning
confidence: 66%
See 1 more Smart Citation
“…The initial conditions for this cluster were generated from the Millennium XXL simulation (Angulo et al 2012) and then rescaled to the latest Wilkinson Microwave Anisotropy Probe-9 (WMAP-9) measurements (Hinshaw et al 2013 , respectively, with a softening length of 1.4 kpc for both particle types. Our mass resolution is ∼1000 times and our spatial resolution is ∼30 times better than those of previous simulations attempting to model anisotropic thermal conduction in a cosmological context (Ruszkowski et al 2011). We also achieve better resolution than idealized non-cosmological simulations with thermal conduction (Ruszkowski & Oh 2010;Parrish et al 2012;Yang & Reynolds 2016) and recent cosmological pure hydrodynamic simulations of clusters (Hahn et al 2017;Rasia et al 2015).…”
Section: Simulationsmentioning
confidence: 66%
“…Recent simulations (Ruszkowski et al 2011;Yang & Reynolds 2016) have shown that thermal conduction alone is not strong enough to offset the cooling losses, even if assuming a full Spitzer conduction coefficient along magnetic field lines. It may, however, provide part of the heating, reducing the burden on the black hole (Yang & Reynolds 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While its inclusion is not expected to change the dynamics of turbulent motions driven by large-scale mergers and accretion on kpc scales (e.g. Xu et al 2009;Ruszkowski et al 2011;Bonafede et al 2011), local amplification of B in shear flows can suppress the growth of instabilities and mixing motions along the spiral arms of sloshing structures (ZuHone et al 2011b) and along AGN-jets (O'Neill & Jones 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al 2009;Ruszkowski et al 2011;Bonafede et al 2011a), local amplification of the magnetic field in shear To resolve the turbulence excited by cluster mergers, sloshing and AGN in the same simulation, one would need to cover scales ranging from R vir 3 Mpc down to the presumed scale of physical dissipation at 0.1 kpc. While its inclusion is not expected to change the dynamics of turbulent motions driven by large-scale mergers and accretion on kpc scales (e.g.…”
Section: Turbulence From Cluster Mergers Active Galacticmentioning
confidence: 99%
“…Various authors have also estimated the amount of turbulence that is produced by the motions of the galaxies through the ICM (Faltenbacher et al 2005;Kim 2007;Ruszkowski et al 2011). In general, cluster galaxies can produce turbulence by two means: (1) As the cold, dense interstellar medium pushes against the external ICM, it produces vorticity, and (2) the gravity of the galaxy causes disturbances in the ICM, similar to dynamic friction.…”
Section: Turbulence By Motions Of Galaxiesmentioning
confidence: 99%